Changes in patient-reported outcomes (PROs) and fecal calprotectin levels in patients with inflammatory bowel disease following a three-week gastrointestinal inpatient rehabilitation - Marina Kuzdas-Sallaberger; Benedikt Steininger; Doreen Stöhr; Monika Mustak-Blagusz; Christoph Mauel (PLoS ONE, 2025)
Background Inflammatory bowel diseases (IBD) pose a considerable burden on patients and society. Rehabilitation programs are increasingly being considered as a complementary treatment. However, empirical evidence on the effectiveness of this approach is still sparse. We therefore investigated changes in patient-reported outcomes and an objective biomarker throughout a three-week inpatient gastrointestinal rehabilitation. Methods We conducted a longitudinal prospective observational study with a pretest-posttest design. Patients completed questionnaires on their subjective health-related quality of life (HRQoL), psychological distress, disease-specific burden, and work ability. Stool samples were collected to determine fecal calprotectin levels. Mean level changes were analyzed by means of t tests for repeated measurements, while differential changes between Crohn’s disease and ulcerative colitis patients were compared using analysis of variance. Results Subjective disease burden and psychological distress decreased over the course of rehabilitation, whereas HRQoL and work ability increased. Fecal calprotectin levels slightly rose and were not meaningfully related to changes in subjective perception of illness. Conclusions We present evidence on rehabilitation as an important treatment in people with IBD in terms of subjective disease burden and various indicators of personal well-being. Furthermore, we advise against the use of fecal calprotectin as a marker for monitoring disease activity in short-term rehabilitation settings.